Elementary Student Conceptual Change About Free Fall Using Reflective Conceptual Change Model - Subuh Anggoro; Ari Widodo; Badarudin Badarudin (Jurnal Penelitian Pendidikan IPA, 2022)
Students and even teachers, particularly in elementary schools, continue to have misconceptions about free fall. When using traditional learning methods, it is difficult to change these misconceptions. The purpose of this article is to reconstruct elementary school students' conceptions using a reflective conceptual change model (RCCM) aided by visual multimedia. The research design is quasi-experimental. The participants in this study were grade 4 elementary school students, 20 of whom were female and 10 of whom were male. A four-tiered test and an observation sheet were used as research instruments. Using data analysis, the findings revealed that all students had a new perspective on free fall. Male students improved their conceptual revisions better than female students. There are 90% of male students experiencing a conceptual change from misconception to scientific conception, compared to 15% of female students. RCCM assisted by visual multimedia can improve students' conception to a higher level